Mathematics and computing : 4th International Conference, ICMC 2018, Varanasi, India, January 9-11, 2018, Revised selected papers /: 4th International Conference, ICMC 2018, Varanasi, India, January 9-11, 2018, Revised selected papers. (2018) - Unknown
No abstract available